Research strategies to discern active psychological therapy components: a scoping review - Leijten, P; Weisz, JR; Gardner, F (SAGE Publications, 2021)
Some clinical scientists are shifting from research on complete named therapy protocols to a more elemental approach—research on specific therapy components that contribute to therapy goals. To characterize and evaluate this emerging field, we systematically searched PsycINFO and Medline for studies evaluating therapy components. We identified 208 studies. In a scoping review, we map, explain, and critically appraise the seven research strategies employed: (a) expert opinion, (b) shared components, (c) associations between the presence of components and therapy effects, (d) associations between fidelity to components and therapy effects, (e) microtrials, (f) additive and dismantling trials, and (g) factorial experiments. Our examination reveals a need for (a) renewed emphasis on experimental trials (vs. meta-analyses testing associations less rigorously), (b) expanded efforts to locate components within the emerging fields of process-based and principle-guided psychotherapy, and (c) a shift from innovative stand-alone studies to development of a coherent science of therapy components.